Role of vacuolar acidification in protein sorting and zymogen activation: a genetic analysis of the yeast vacuolar proton-translocating ATPase. - Yamashiro, C T (1990)
Vacuolar acidification has been proposed to play a key role in a number of cellular processes, including protein sorting, zymogen activation, and maintenance of intracellular pH. We investigated the significance of vacuolar acidification by cloning and mutagenizing the gene for the yeast vacuolar proton-translocating ATPase 60-kilodalton subunit (VAT2). Cells carrying a vat2 null allele were viable; however, these cells were severely defective for growth in medium buffered at neutral pH. Vacuoles isolated from cells bearing the vat2 null allele were completely devoid of vacuolar ATPase activity. The pH of the vacuolar lumen of cells bearing the vat2 mutation was 7.1, compared with the wild-type pH of 6.1, as determined by a flow cytometric pH assay. These results indicate that the vacuolar proton-translocating ATPase complex is essential for vacuolar acidification and that the low-pH state of the vacuole is crucial for normal growth. The vacuolar acidification-defective vat2 mutant exhibited normal zymogen activation but displayed a minor defect in vacuolar protein sorting.